Strengthening the quality of paediatric primary care: protocol for the process evaluation of a health systems intervention in South Africa. (23rd October 2018) - Murdoch, Jamie; Curran, Robyn; Bachmann, Max; Bateman, Eric; Cornick, Ruth Vania; Doherty, Tanya; Picken, Sandra Claire; Simelane, Makhosazana Lungile; Fairall, Lara
Abstract : Background: Despite significant reductions in mortality, preventable and treatable conditions remain the leading causes of death in children under five within South Africa. The WHO's Integrated Management of Childhood Illness (IMCI) programme has been widely implemented to address the most common causes of mortality in children under five. Although effective, limitations in IMCI scope and adherence have emerged. The Practical Approach to Care Kit (PACK) Child guide has been developed to expand on IMCI and address these limitations. It is intended as a clinical decision support tool for health workers with additional systems strengthening components, including active implementation and training strategy to address contextual and organisational factors hindering quality of care for children. Implementation is complex, requiring comprehensive pilot and process evaluation. The PACK Child pilot and feasibility study will sample 10 primary care facilities in the Western Cape Province. Staff will be trained to integrate the PACK Child guide into routine practice. The process evaluation will investigate implementation and health systems components to establish how to optimise delivery, strengthen IMCI principles and factors required to support effective and sustained uptake into everyday practice. Methods: Mixed method process evaluation. Qualitative data include interviews with managers, staff, caregivers and policymakers; observations of training, consultations and clinic flow. Quantitative data include training logs and staff questionnaires. Quantitative and qualitative analysis will be integrated to describe study sites and develop explanations for implementation variation. Discussion: The process evaluation will provide the opportunity to document implementation and refine the programme prior to a larger pragmatic trial or scale-up.